Identifikasi Kandungan Merkuri (Hg) dan Tingkat Keasaman (pH) pada Sungai Takaras Terdampak Aktifitas Pertambangan Emas di Kecamatan Rakumpit - Lisa Virgiyanti; Amru Ash Shodaq; Fahrul Indrajaya; Neny Fidayanti; Neny Sukmawatie (Pusat riset dan Inovasi Nasional, 2026)
Takaras River is a river basin that is vulnerable to pollution, particularly from the mercury usage in small-scale gold mining. This study aims to identify water quality based on mercury (Hg)and pH levels in the Takaras River. Samples were taken at two locations using a purposive sampling method. Results showed indications of mercury use on former gold mining land around the Takaras River altought the mercury content level was below 0.075 µg/L or 0.00075 mg/L in sample 1 and 2. Based on the test results, the acidity level (pH) in the two water samples from Takaras River is 3.86 and 3.84 in sample 1 and 2, compared to the maximum pH quality standard of 6-9 for Class II water, it is concluded that the scale of acidity in Takaras River is very low, indicating that the water quality in the Takaras River is highly acidic, abnormal, and shows signs of serious pollution. The implications of low pH levels in the Takaras River can cause damage to the Takaras River ecosystem, a decline in soil quality and fertility, and an increase in heavy metal toxicity in the environment surrounding the river.